Modulating the reaction pathway of phenyl diazonium ions using host–guest complexation with cucurbit[7]uril. Issue 22 (24th February 2022) - Moorthy, Suresh; Castillo Bonillo, Alvaro; Lambert, Hugues; Kalenius, Elina; Lee, Tung-Chun
Abstract : Encapsulation of a phenyl diazonium ion inside cucurbit[7]uril can effectively inhibit its reaction with water molecules while preserving its reactivity in diazo coupling reactions. Abstract : Aryl diazonium ions are known to be an important intermediate in the divergent synthesis of azo compounds and substituted aromatics. The presence of more than one electrophilic center in a diazonium ion could lead to undesirable side reactions during a synthesis. Herein, we report that the electrophilic α-carbon on a phenyl diazonium [PhN2 ] + ion can be selectively deactivated upon host–guest complexation with cucurbit[7]uril (CB7) in aqueous media, achieving a ∼60-fold increase in the half-life of [PhN2 ] + . Notably, however, the electrophilic nitrogen of the encapsulated diazonium ion remains active towards diazo coupling with strong nucleophiles, allowing the formation of azo compounds using a two-month-old aqueous solution of [CB7–PhN2 ] + . Our supramolecular approach can open new possibilities for the reactive chemistry of organic molecules in aqueous media.